Odpowiedź :
Odpowiedź:
3 - 4/7- 2 i 3/7= 3- 2 i 7/7= 3-3=0
5 i 9/11 - 3 i 5/11= 2 i 4/11
10 i 15/17- 4 i 9/17= 6 i 6/17
7 i 7/9- 4 i 2/9= 3 i 5/9
11 i 10/11- 7 i 4/11= 4 i 6/11
12 i 4/19- 8 i 3/19= 4 i 1/19
17 i 11/14- 9 i 6/14= 8 i 5/14
15 i 7/12- 9 i 2/12= 6 i 5/12
9 i 14/27- 4 i 10/27= 5 i 4/27
20 i 7/13- 15 i 4/13= 5 i 3/13
5 i 23/31- 3 i 15/31= 2 i 8/31
16 i 17/23- 7 i 8/23= 9 i 9/23
Szczegółowe wyjaśnienie:
Odpowiedź:
3 - 4/7 - 2 3/7 = 3 - 3 = 0
5 9/11 - 3 5/11 = 2 4/11
10 15/17 - 4 9/17 = 6 6/17
7 7/9 - 4 2/9 = 3 5/9
11 10/11 - 7 4/11 = 4 6/11
12 4/19 - 8 3/19 = 4 1/19
17 11/14 - 9 6/14 = 8 5/14
9 14/27 - 4 10/27 = 5 4/27
20 7/13 - 15 4/13 = 5 3/13
3 23/31 - 3 15/31 = 8/31
16 17/23 - 7 8/23 = 9 9/23
Szczegółowe wyjaśnienie: